2002
DOI: 10.2135/cropsci2002.1475
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Selection for Partial Resistance to Crown Rust in Oat

Abstract: the absence of significant genetic interactions between host and pathogen genotypes (Parlevliet, 1985), the use Crown rust (caused by the fungus Puccinia coronata Cda. f. sp.of this type of resistance in crop cultivars should prevent avenae Eriks.) is a major disease of cultivated oat (Avena sativa L.). Partial resistance is a form of incomplete resistance characterized by a major shifts in the composition of the pathogen populareduced rate of epidemic development and is potentially more durable tion increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…However, Pc68/5*Starter is a near isogenic line and might have another resistance gene in addition to Pc68, which would originate from the cultivar Starter. This cultivar demonstrated a degree of resistance upon release in the U.S. (Stuthman et al, 1990), but now it is considered highly susceptible (Díaz-Lago et al, 2002;Leonard, 2002;Leonard, 2003). If the additional gene for resistance was from the genotype Pc68/5*Starter, the resistant recombinant lines would be expected to exhibit levels of FS and AUDPC*c that would be very similar to the resistant parent.…”
Section: Discussionmentioning
confidence: 99%
“…However, Pc68/5*Starter is a near isogenic line and might have another resistance gene in addition to Pc68, which would originate from the cultivar Starter. This cultivar demonstrated a degree of resistance upon release in the U.S. (Stuthman et al, 1990), but now it is considered highly susceptible (Díaz-Lago et al, 2002;Leonard, 2002;Leonard, 2003). If the additional gene for resistance was from the genotype Pc68/5*Starter, the resistant recombinant lines would be expected to exhibit levels of FS and AUDPC*c that would be very similar to the resistant parent.…”
Section: Discussionmentioning
confidence: 99%
“…The use of recurrent selection for partial resistance in oat as a means to provide protection against Pca has been reported in several studies (Díaz-Lago et al 2002 ;Long et al 2006 ). Among the various resistance breeding strategies, Holland and Munkvold ( 2001 ) considered gene pyramiding and selection for partial resistance to be more advantageous than single gene resistance and complete resistance (race-specifi c).…”
Section: Genetic Resistancementioning
confidence: 99%
“…A number of breeding techniques are recommended to acquire durable resistance. Among these are recurrent selection, which, by defi nition, is increasing the frequency of desirable alleles and consequently gains in the population due to repeated cycles of selection and recombination of selected lines (Díaz-Lago et al 2002 ). The authors demonstrated the usefulness of rapid cycle recurrent selection as a population improvement procedure capable of effectively increasing the level of partial resistance to crown rust in an adapted and high-yielding oat population.…”
Section: Rustmentioning
confidence: 99%
“…Breeding for complete racespecific resistance has been the primary control measure for this disease (Simon 1985). However, this strategy usually provides protection for limited period of time (Diaz-Lago et al 2002). Alternative types of resistance, capable of providing longer lasting cultivars, are necessary, and partial resistance is currently being explored as one.…”
Section: Introductionmentioning
confidence: 99%